Internalisasi Karakter Berkebhinekaan Global melalui Ekstrakurikuler Tapak Suci - Fadhilatus Sakdiyah; Suprihno Suprihno (Journal on Education, 2024)
This research aims to describe how to internalize the character of global diversity with tapak suci extracrurriculars. This research method uses descriptive qualitative. The location chosen was MTs Muhammadiyah Bandung. Informants who participated were madrasa heads, tapak suci trainers guidance and conseling teachers, and class VII students. The data collection techniques applied were interviews, observation, and documentation. Meanwhile, data analysis applies the Miles and Hubberman model analysis technique by starting with data collection, reduction, presentation and drawing conclusions. Based on the results of data analysis and discussion, it can be concluded that the internalization of the character of global diversity through the tapak suci extracurricular at MTs Muhammadiyah Bandung gave birth to the following 3 characters: tolerance towards understanding and appreciation regarding cultural heritage carried out through coaching, direction and advice methods; Skills in interpersonal communication are carried out through habituation and supervision methods; and Personal and social responsibility is carried out through methods of habituation, example, and punishment.